- #1

Foon

- 5

- 0

Consider the general reaction:

2A + B --> 2E + F

The experimentally determined rate law equation is written as follows:

Rate = k[A]

A proposed mechanism for the reaction has the first step below:

Step 1: A + B --> C + F (rate determinging step)

Assuming a two-step mechanism, write a possible second elementary reaction for this mechanism.

And this is what I have but I'm not sure if its right. And I'm totally puzzled as to how they get rid of the C.

Step1: A + B --> C + F

Step2: A --> C- + 2E

------------------------

2A + B --> 2E + F

It has to be totally wrong since they've given me a rate law which I have no idea how to use.

A proposed mechanism for the reaction has the first step below:

Step 1: A + B --> C + F (rate determinging step)

Assuming a two-step mechanism, write a possible second elementary reaction for this mechanism.

And this is what I have but I'm not sure if its right. And I'm totally puzzled as to how they get rid of the C.

Step1: A + B --> C + F

Step2: A --> C- + 2E

------------------------

2A + B --> 2E + F

It has to be totally wrong since they've given me a rate law which I have no idea how to use.